Bleed or Clot? Managing Bleeding in Post Thrombolysis Patient with Massive Pulmonary Embolism Who Underwent Recent Major Cancer Surgery - Balakrishnan, Sivasubramaniam; Mohamad Zahir , Mohd Zulkifli; Draman, Che Rosle; Wan Ali, Wan Ahmad Syahril Rozli; Ibrahim, Ismail (IIUM Medical Journal Malaysia, 2022)
51 years old female, with invasive left breast cancer stage T3N0M0 developed syncope, hypotension, chest pain, and ST elevation in anterior leads on the next day following Left Mastectomy. The initial diagnosis of AMI revised to massive pulmonary embolism after tranthoracic enchocardiogram. However, IV (intravenous) Metalyse was given as thrombolysis therapy and the patient showed a good initial response. Subsequently, the patient developed massive bleeding from the surgical site. Bleeding was successfully controlled with total of 11 units packed cells, 4 units fresh frozen plasma, 4 units of platelet, and 6 units of cryoprecipitate as well as prothrombin complex concentrate. Local compression bandage and continuous surgical site drainage were applied in this case. Following successful control in bleeding unfractionated heparin infusion was given for 2days followed by low molecular weight heparin for 2days and discharged with a direct oral anticoagulant. On follow up visit, the patient made an excellent recovery and planned for further treatment for breast cancer. Thrombolysis therapy and anticoagulant therapy in post-operative patients with high-risk bleeding posses great challenges. Careful evaluation of bleeding versus clotting is the key to good outcomes.